2018
DOI: 10.1038/eye.2017.305
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intravitreal injection of ranibizumab in early pregnancy: a series of three cases

Abstract: PurposeRanibizumab is used in the treatment of choroidal neovascularization (CNV). Although systemic exposure to ranibizumab is low after ocular administration, its mechanism of action must be regarded as potentially teratogenic and embryo-fetotoxic. Women are advised to wait 3 months after the last dose of treatment with ranibizumab before conceiving. Little is known about the fetal side-effects of this drug.MethodsThree pregnant women were treated with ranibizumab. One patient had idiopathic CNV.ResultsAfter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 4 publications
0
12
0
3
Order By: Relevance
“…The half-life of intravitreal bevacizumab in a human was estimated to be 6.7–10 d depending on the use of either a one-compartment model or two-compartment model[ 65 - 68 ], while the half-life of bevacizumab in human serum is 17–21 d, similar to that of other full-length antibodies. Intravitreal aflibercept has a half-life of 4.7 d in rabbits[ 69 ] and an estimated 9 d in humans based on the intermediate size of the molecule (between ranibizumab and bevacizumab), while bound aflibercept in human serum has a half-life of 18 d[ 70 ]. Table 1 summarizes the structural and pharmacokinetic characteristics of the four anti-VEGF drugs.…”
Section: Preparing For Dr Progression In Pregnant Diabeticsmentioning
confidence: 99%
See 2 more Smart Citations
“…The half-life of intravitreal bevacizumab in a human was estimated to be 6.7–10 d depending on the use of either a one-compartment model or two-compartment model[ 65 - 68 ], while the half-life of bevacizumab in human serum is 17–21 d, similar to that of other full-length antibodies. Intravitreal aflibercept has a half-life of 4.7 d in rabbits[ 69 ] and an estimated 9 d in humans based on the intermediate size of the molecule (between ranibizumab and bevacizumab), while bound aflibercept in human serum has a half-life of 18 d[ 70 ]. Table 1 summarizes the structural and pharmacokinetic characteristics of the four anti-VEGF drugs.…”
Section: Preparing For Dr Progression In Pregnant Diabeticsmentioning
confidence: 99%
“…Several studies on the use of ranibizumab and bevacizumab in pregnant women have been reported of which some have been summarized by Polizzi and Mahajan[ 31 ]. Most of the studies in pregnant women are case reports, and initial intravitreal ranibizumab was given either 8–17 wk post last menstrual period (LMP)[ 70 ] or in the third trimester[ 71 , 72 ]; all reported no complications.…”
Section: Preparing For Dr Progression In Pregnant Diabeticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Women of childbearing age are advised to wait 3 months after the last dose before conceiving. 18 For pregnant women who develop signficant macular oedema and are at risk of irreversible vision loss, ophthalmology review and counselling regarding the potential risks versus benefits is mandated. 19,20 If anti-VEGF drugs are to be used, then ranibizumab may be preferable to bevacizumab or aflibercept because it suppresses plasma VEGF levels to a lesser degree.…”
Section: Diabetic Eye Diseasementioning
confidence: 99%
“…However, these studies did not specifically investigate patients with MFC and PIC, but noninfectious uveitis in general. Since anti-VEGF is considered to be potentially teratogenic and embryofetotoxic, treatment with intravitreal anti-VEGF injections is advised to be avoided in pregnancy, especially in the first trimester (Polizzi & Mahajan 2015;Peracha & Rosenfeld 2016;Fossum et al 2018). Therefore, it is of utmost importance to prohibit the development or reactivation of CNV during pregnancy in patients with MFC and PIC.…”
Section: Introductionmentioning
confidence: 99%